PROCEDURAL FEATURES OF THE ALBANIAN CASE LAW ON RECOGNITION AND ENFORCEMENT OF FOREIGN ARBITRAL AWARDS - Spahiu, Artan (European Scientific Journal, ESJ, 2015)
The internationalization of goods and services in the last decades have underscored the importance of international commercial arbitration and its enforcement mechanism of the foreign awards. The recognition and enforcement of foreign arbitral awards under the jurisdiction of a state, is mostly provided through the effect of the New York Convention (1958), which is sanctioned today in 146 countries worldwide. Albania has become part of this large group of states which have voluntarily chosen to share the unquestionable values established by the New York Convention in the field of international commercial arbitration. But despite the formal aspect, Albanian jurisprudence clearly shows an unconsolidated experience of the Albanian judiciary in the field of recognition of foreign arbitral awards. This is not only because of the short time coexistence of the Albanian legal order with the Convention, but also because of a limited knowledge of traders on the instruments established by the Convention and because of the judicial system indifference demonstrated toward the Convention traditional interpretation. This article aims to bring in the spotlight the features manifested by the Albanian jurisprudence, regarding the procedural aspects of the recognition of foreign arbitral awards. These aspects have been found by the research of several judicial decisions of the Court of Appeals, upon the requests for recognition of foreign arbitral awards.